Effects of Pulverized Composting Methods on the Early Growth and Development of Khaya senegalensis in Maiduguri, Nigeria - Musa, Garba; Dishan, Edward Ephraim; Gupa, Mohammed Alimu (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
This study evaluated the effects of pulverized composting methods surface and subsurface on the early growth and development of Khaya senegalensis in Maiduguri, Nigeria. Foliage from Khaya senegalensis, Gmelina arborea, Syzygium cumini, and Ziziphus spina-christi was collected within the University of Maiduguri premises, sundried, and pulverized using a motorized disc refiner. The pulverized materials were categorized as composting treatments (M1–M4) and subjected to decomposition for 30, 60, and 90 days at both surface (0 cm) and subsurface depths (45 cm, 60 cm, and 75 cm). Macro (N, P, K, Ca, Mg) and micro (Mn, Cu, Zn, Fe) nutrient compositions were analyzed before and after the 90-day composting period. Potting media were prepared using river sand and compost in a 3:1 ratio. Seeds of Khaya senegalensis were sown at a depth of 3 cm, and growth parameters number of leaves (NOL), stem height (SHT), and stem diameter (SDM) were monitored weekly. Data were analyzed using ANOVA, regression, t-tests, and LSD for mean separation. Results indicated that compost derived from Gmelina arborea consistently yielded the lowest values for growth parameters over the eight-week period. Significant differences were observed in developmental traits such as root length, plant fresh and dry weights, root and leaf fresh weights, turgid weight, and leaf area, while root dry weight did not differ significantly across treatments. Analysis of composting methods revealed no significant differences (p < 0.05) in stem height and stem diameter throughout the observation period, though a variation in leaf number was noted at week six. This discrepancy may be attributed to differences in microbial activity and nutrient mineralization across composting methods.